Hypothetical Aspect of Crowdfunding as Alternate Finance for University Spinoffs and Quadruple Helix - Kuma, Francis Kwaku; Yosuff, Mohd Effandi (Journal of Research Management and Governance, 2020)
In this study, we address the finance gaps that threaten the operations of University Spinoffs (USOs), by examining the financing options available to sustain their activities. The study thus discusses crowdfunding as alternate finance to address these financial gaps using the quadruple helix model of innovation. The study combines theoretical perspectives of the quadruple helix model with the practical aspects of USOs raising finance using the crowd. We examine the internal and external financing sources for USOs and explain theoretically, why USOs can rely on crowdfunding as alternate finance. The key concepts of the concept are critically considered, and the study is thus conducted in the form of a review of literature and expression of opinion. Accordingly, the empirical justification of the concept presented is not within the scope of this paper.